Does Ellen DeGeneres adopt rhetorical strategies in her talk show’s monologues for verbal humor? - Zhou, Tianli; Mansor, Nor Shahila; Lay, Hoon Ang; Sharmini, Sharon (JLLS, 2022)
Verbal humor is a prominent characteristic of talk shows, which has inspired many humor linguists’ study enthusiasms from a variety of perspectives. Nevertheless, the rhetorical strategies adopted by the host to achieve verbal humor in talk shows are always complex and not easy to understand by the audience. What’s more, the literature on this point is scanty. To address the gap, the current research tries to examine the rhetorical strategies in the host’s verbal humor on the Ellen talk show. Sixteen monologues from the Ellen talk show were selected as data resources. After the data was transcribed, the rhetorical fragments that made the audiences laugh were coded as data, and NVivo was used as the main instrument in the study’s process of coding and analysing. The findings of the present study reveal that Ellen DeGeneres adopts eighteen kinds of rhetorical strategies to achieve verbal humor in her sixteen monologues: exaggeration, facetiousness, personification, satire, simile, over literalness, metaphor, puns, bombast, ridicule, irony, repartee, misunderstanding, insults, analogy, definition, infantilism, and allusion. Ellen tends to produce verbal humor with the type of single rhetorical strategy, but she also adopts the type of two or three mixed rhetorical strategies to produce verbal humor occasionally. Moreover, the use of rhetorical strategies in samples is unevenly distributed, and the data suggest that Ellen prefers to use the rhetoric of exaggeration, facetiousness, and satire more frequently than other rhetorical strategies.